2018
DOI: 10.4236/ojemd.2018.82007
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, Clinical and Therapeutic Characteristics of Hypertensive Type 2 Diabetics at the Marc Sankale Center of Dakar

Abstract: Introduction: High blood pressure (hypertension) and diabetes mellitus are two major risk factors for cardiovascular disease, which is increasing rapidly in Africa and worldwide. Africa has the highest prevalence rate of hypertension in the world, with 46% of adults over the age of 25 with. Hypertension is common in type 2 diabetes and increases cardiovascular risk. The association of these two pathologies has many particularities in the sub-Saharan subject. The work related to this entity in Africa shows a fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Hypertension and diabetes mellitus are the leading risk factors for cardiovascular diseases, which are increasing rapidly throughout the world [1]. Hypertension is a type of non-communicable disease that remains a health problem in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension and diabetes mellitus are the leading risk factors for cardiovascular diseases, which are increasing rapidly throughout the world [1]. Hypertension is a type of non-communicable disease that remains a health problem in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, diabetes was present in 23% of volunteers. Sow et al [27] in their study found overweight in 30.3% and obese in 22.5%. In Ka et al's study, the rates of obesity and overweight were 5.9% and 2.4% respectively [28].…”
Section: Discussionmentioning
confidence: 86%
“…This may be related to an increased catabolic rate of proteins for energy production in the body and a decrease in GFR. This process of proteolysis is explained by the fact that in energy failure due to the non-use of blood glucose, the cells seek other sources of supply among which the proteins by their degradation can release the substrates of the gluconeogenesis and amino wastes such as urea and creatinine as described by previous studies [ 14 ]. This led to moderate and severe terminal renal failure in patients, respectively, at 1.6% and 29.5% with a p-value of 0.876.…”
Section: Discussionmentioning
confidence: 99%